Deacetylation by SIRT1 Reprograms Inflammation and Cancer - Liu, Tie Fu (SAGE Publications, 2013)
NAD(+)-dependent deacetylase SIRT1 is a master regulator of nucleosome positioning and chromatin structure, thereby reprogramming gene expression. In acute inflammation, chromatin departs from, and returns to, homeostasis in an orderly sequence. This sequence depends on shifts in NAD(+) availability for SIRT1 activation and deacetylation of signaling proteins, which support orderly gene reprogramming during acute inflammation by switching between euchromatin and heterochromatin. In contrast, in chronic inflammation and cancer, limited availability of NAD(+) and reduced expression of SIRT1 may sustain aberrant chromatin structure and functions. SIRT1 also influences inflammation and cancer by directly deacetylating targets like NFκB p65 and p53. Here, we review SIRT1 in the context of inflammation and cancer.